Effect of cocaine on striatal dopamine clearance in a rat model of developmental stress and attention-deficit/hyperactivity disorder. (2nd January 2016) - Womersley, Jacqueline S.; Kellaway, Lauriston A.; Stein, Dan J.; Gerhardt, Greg A.; Russell, Vivienne A.
Abstract: Attention-deficit/hyperactivity disorder (ADHD) and developmental stress are considered risk factors for the development of drug abuse. Though the physiological mechanisms underlying this risk are not yet clear, ADHD, developmental stress and drug abuse are known to share underlying disturbances in dopaminergic neurotransmission. Thus, we hypothesized that clearance of cocaine-induced elevations in striatal dopamine would be prolonged in a rat model of ADHD and that this would be further increased by exposure to developmental stress. In the current study, male spontaneously hypertensive rats (SHRs), a well-validated model of ADHD, and control Wistar-Kyoto (WKY) rats were exposed to either standard rearing (nMS) or a maternal separation (MS) paradigm involving removal of the pups from the dam for 180 min/day over 13 days. This produced a 2 × 2 factorial design (SHR/WKY × nMS/MS) with 5–6 rats/group. Striatal clearance of exogenously applied dopamine was measured via in vivo chronoamperometry, and the difference in dopamine uptake parameters before and after cocaine administration was compared between experimental groups. Cocaine, a potent dopamine transporter inhibitor, reliably increased the clearance time of dopamine though no difference in this parameter was found between SHR and WKY strains. However, developmental stress elevated the cocaine-induced increase in time to clear 50% of exogenously applied dopamine ( T 50 ) in SHR but had no effect in WKY rats. These findings suggest that a strain × environment interaction prolongs elevated levels of dopamine thereby potentially increasing the rewarding properties of this drug in SHR.